2020
DOI: 10.1101/2020.09.22.20198754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnic differences in COVID-19 infection, hospitalisation, and mortality: an OpenSAFELY analysis of 17 million adults in England

Abstract: Background: COVID-19 has had a disproportionate impact on ethnic minority populations, both in the UK and internationally. To date, much of the evidence has been derived from studies within single healthcare settings, mainly those hospitalised with COVID-19. Working on behalf of NHS England, the aim of this study was to identify ethnic differences in the risk of COVID-19 infection, hospitalisation and mortality using a large general population cohort in England. Methods: We conducted an observational cohort s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…In line with existing studies investigating ethnic inequalities in SARS-CoV-2 infection and COVID-19 mortality [15,3,4,16,17], we find that most ethnic minority groups were disproportionally affected in the first wave. Our findings that the ethnic inequalities in COVID-19 mortality differed between the two waves is consistent with the evidence that these disparities are likely to be driven by differences in exposure to infection and therefore can change over time.…”
Section: Comparison With Related Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…In line with existing studies investigating ethnic inequalities in SARS-CoV-2 infection and COVID-19 mortality [15,3,4,16,17], we find that most ethnic minority groups were disproportionally affected in the first wave. Our findings that the ethnic inequalities in COVID-19 mortality differed between the two waves is consistent with the evidence that these disparities are likely to be driven by differences in exposure to infection and therefore can change over time.…”
Section: Comparison With Related Studiessupporting
confidence: 91%
“…A recent systematic review of 50 studies have showed that people from ethnic minority background in the UK and other countries, particularly Black and South Asian groups, have been disproportionately affected by the Coronavirus (COVID-19) pandemic compared to people of White ethnic background [1] While several studies have investigated whether adjusting for sociodemographic and economic factors and medical history reduces the estimated difference in risk of mortality and hospitalisation [2,3,4], the reasons for the differences in the risk of experiencing harms from COVID-19 are still being explored during the course of the pandemic. Factors including structural racism [5,6], social vulnerability [7,8] social and material deprivation, [9] have widely been suggested as potential mechanisms for these reported inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of our study is that certain diseases (cancer, haematological malignancies and neurologic diseases) and specific states of a disease (obesity class, former or current smoker and control of diabetes, hypertension and asthma) which increase the risk of dying from COVID-19 [11] were not studied since they are not provided in the datasets. Furthermore, we were not able to study other social determinants and population factors which could be having an important impact in patient outcomes [39, 40]. However, our model accounts for the main risk factors associated with death in patients with COVID-19, and not requiring inputting specific disease states makes it easier to be used by clinicians while minimising the risk of not having enough data to use the score with precision.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic, caused by the highly infectious SARS-CoV-2 virus, represents an unprecedented global health crisis 1,2 . Death from COVID-19 is associated with male gender, older age, Asian/Black ethnicity, and coexisting conditions including cardiovascular disease and obesity 3,4 . Guided by international recommendations from the World Health Organization (WHO), public health risk mitigating measures such as social/physical distancing were introduced early in the pandemic to limit community transmission of COVID-19 [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%